Differential lead-fluoride and nickel-fluoride uptake in co-polluted soil variably affects the overall physiome in an aromatic rice cultivar. (1st January 2021) - Banerjee, Aditya; Roychoudhury, Aryadeep
Abstract: The present study aimed to show that nickel and fluoride exhibited synchronized co-inhibited uptake in the aromatic rice cultivar, Gobindobhog, since bioaccumulation of the two elements was lower than that during individual stress, so that overall growth under combined stress was similar to control seedlings. On the contrary, lead and fluoride stimulated their co-uptake which triggered oxidative damages, NADPH oxidase activity, methylglyoxal accumulation, photosynthetic inhibition, membrane-protein damages, necrosis and genomic template degradation. Accumulation of proline, anthocyanins, non-protein thiols and phytochelatins was stimulated for systemic protection against reactive oxygen species (ROS) and xenobiotic-mediated injuries during lead-fluoride toxicity. ROS accumulation during nickel-fluoride stress was insignificant due to which enhanced accumulation of most antioxidants was not required. Glutathione depletion during combined lead-fluoride toxicity was due to its utilization in the glyoxalase cycle and also inhibition of glutathione reductase. However, the nickel-fluoride-treated sets maintained glutathione reserves and glyoxalase activity similar to those in control. Presence of fluoride 'safeguarded' the glutathione-utilizing enzymes like glutathione reductase, glutathione peroxidase and glutathione-S-transferase during dual lead-fluoride stress. This was because these enzymes showed higher activity compared to that under lead toxicity alone. Enzymatic antioxidants like superoxide dismutase, ascorbate peroxidase and guaiacol peroxidase were activated during lead-fluoride toxicity due to altered iron and copper homeostasis. Catalase activity was strongly inhibited, resulting in the inability to scavenge H2 O2 and suppression of the fluoride-adaptable phenotype. However, none of the enzymatic antioxidants were inhibited during nickel-fluoride stress, which cumulatively allowed the seedlings to maintain normal physiology. Overall our findings holistically reveal the physiological plasticity of Gobindobhog in response to two different heavy metals under the influence of fluoride. Graphical abstract: Image 1 Highlights: Increased lead and fluoride co-uptake triggered severe oxidative damages in rice. Accumulation of ROS-induced genomic template degradation and necrosis. Nickel and fluoride exhibited co-inhibited uptake. Growth and physiology under combined nickel-fluoride stress was almost unaffected. Extent of toxicity was: Combined lead-fluoride > nickel > lead > fluoride > nickel-fluoride. Abstract : Main finding: The investigation revealed the ameliorative potential of Ni to reduce fluoride bioaccumulation and the environmental concerns of safe rice cultivation in Pb and fluoride co-polluted sites, since co-existence of Pb and fluoride would be disastrous for rice cultivation as well as consumer health.